Epistemological bases of UCPR student and professors research groups 2004 (2021)
The new conception in business administration education has two moments: the first is epistemological, in a Department that considers students as included in the relation education-researchsocial projection. The second is social cohesion, understood as the mechanisms that tie individuals and groups to the social dynamic, thereby creating a sense of social belonging. Student and professor research groups recreate the notion of a community of learning and should share the same cooperation and communication principles.